Preliminary design exploration of prospective multirotor aerobots - Youhanna, Vishal; Felicetti, Leonard; Ignatyev, Dmitry (International Council of the Aeronautical Sciences (ICAS), 2024)
The groundbreaking success of NASA's Ingenuity Helicopter has spurred immense potential for Martian exploration, emphasizing the pivotal role of aerobots alongside rovers and landers. However, the helicopter's limitations, stemming from its compact and simplistic design, are apparent in its restricted long-range endurance and payload capacity. This paper suggests a feasible optimisation approach for Martian rotorcraft concepts while addressing constraints and progressing Martian drone technology. The key focus lies in improving performance to meet the evolving demands of forthcoming Martian aerobot missions. Based on a comprehensive parametric analysis rooted in simplified rotorcraft momentum theory, this study focuses on power requirements of rotorcrafts with single, coaxial, tandem, quad and hexa rotors for hover, vertical climb, and forward flight segments. Modified to meet more demanding mission criteria, these designs are limited by the spacecraft aeroshell's maximum size for safe transport to Mars. Among the considered configurations, the hexacopter emerged as the most efficient choice, offering a balance between performance, endurance, and payload capacity, while a conventional single main rotor configuration fell short within the specified parameters.
Keywords: Martian Aerial Drones; Planetary UAV; Rotorcraft Conceptual Design